Ambiphilic cross-coupling with aryl-bismuth reagents - Byeongdo Roh; Benedict A. Williams; Josep Cornella (Nature, 2026)
Abstract Cross-coupling reactions traditionally permit the formation of Ar-Ar bonds between an aryl nucleophile and an aryl electrophile under transition-metal catalysis 1,2 . The high selectivity of the myriad of couplings known to date relies on a tailored combination of nucleophilic and electrophilic coupling partners, enabled by the mechanistic distinction between nucleophiles and electrophiles, which undergo fundamentally different catalytic steps 3 . Here we report ambiphilic aryl-bismuth reagents that can behave as either nucleophiles or electrophiles in transition-metal-catalysed cross-couplings, fundamentally breaking from this dichotomy in reactivity. Their ambiphilic reactivity arises from their ability to engage in both oxidative addition and transmetalation processes with transition-metal complexes, as demonstrated by stoichiometric and mechanistic studies. By demonstrating that a single aryl reagent can engage in both canonical elementary steps, this work challenges the long-standing assumption that intrinsic bond polarity rigidly dictates the mechanistic role in cross-coupling chemistry.